Alpha adrenergic receptor blockade increases capillarization and fractional O2 extraction and lowers blood flow in contracting human skeletal muscle. (11th April 2017) - Mortensen, S. P.; Egginton, S.; Madsen, M.; Hansen, J. B.; Munch, G. D. W.; Iepsen, U. W.; Åkerström, T.; Pedersen, B. K.; Hellsten, Y.
Abstract: Aim: To assess the effect of elevated basal shear stress on angiogenesis in humans and the role of enhanced skeletal muscle capillarization on blood flow and O2 extraction. Methods: Limb haemodynamics and O2 extraction were measured at rest and during one‐leg knee‐extensor exercise (12 and 24 W) in 10 healthy untrained young men before and after 4‐week treatment with an α1 receptor‐antagonist (Terazosin, 1–2 mg day −1 ). Corresponding biopsies were taken from the m. vastus lateralis . Results: Resting leg blood flow was increased by 57% 6 h following Terazosin treatment ( P < 0.05), while basal capillary‐to‐fibre ratio was 1.69 ± 0.08 and increased to 1.90 ± 0.08 after treatment ( P < 0.05). Leg O2 extraction during knee‐extensor exercise was higher (4–5%; P < 0.05), leg blood flow and venous lactate levels lower (6–7%; P < 0.05), while leg VO2 was not different after Terazosin treatment. Conclusions: These results demonstrate that daily treatment with an α‐adrenergic receptor blocker induces capillary growth in human skeletal muscle, likely due to increased shear stress. The increase in capillarization resulted in an increased fractional O2 extraction, a lower blood flow and venous lactate levels in the exercising leg. The increase in capillarization, and concomitant functional readouts in the exercising leg, may provide a basis for novel angiotherapy.